Highly Responsive and Thermally Reliable Near‐Infrared Organic Photodiodes Utilizing Naphthalocyanine Molecules Tuned with Axial Ligands. Issue 4 (4th December 2020) - Leem, Dong‐Seok; Lee, Kwang‐Hee; Li, Ning; Park, Bum Woo; Choi, Taejin; Ro, Takkyun; Kwon, Oh Kyu; Kwon, Young‐Nam; Ng, Tse Nga; Kim, Sunghan
Abstract: Achieving high‐performance near‐infrared (NIR) photodiodes is in great demand for potential applications like biometrics, security, artificial vision, biomedical imaging, etc. Herein, silicon naphthalocyanine (SiNc) small molecule‐based NIR photodiodes with narrowband absorption are presented. The optimized photodiode by varying the axial ligand in the SiNc molecules exhibits a high external quantum efficiency of 76.6% at 795 nm with narrow full width at half maximum of 80 nm, a very low dark current of 1.07 nA cm −2 at a reverse bias of −3 V, and the resultant detectivity of 5.66 × 10 12 Jones. Further increase of the detectivity up to 10 13 Jones is obtained by modulating the applied bias to −1 V, which is among the highest values of organic NIR detectors reported to date. The SiNc‐based photodiodes are further characterized by temporal response, linear dynamic range, etc., and shown to be stable in high humidity for over a month and in a remarkably wide temperature range (−55 to 125 °C). It is highly likely that the developed SiNc‐based photodiodes can be applicable to a wide variety of NIR sensor platforms. Abstract : High performance near‐infrared (NIR) organic photodiodes with silicon naphthalocyanine small molecules are demonstrated. The optimized devices exhibit high efficiency over 76% in the NIR wavelength, low noise characteristics, and long‐term reliability in humidity condition as well as a wide temperature range, which can be applicable to a variety of NIR sensor platforms.